2017
DOI: 10.1038/jp.2017.105
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of critical congenital heart defects screening using pulse oximetry in the neonatal intensive care unit

Abstract: Objective:To evaluate the implementation of early screening for critical congenital heart defects (CCHDs) in the neonatal intensive care unit (NICU) and potential exclusion of sub-populations from universal screening.Study Design:Prospective evaluation of CCHD screening at multiple time intervals was conducted in 21 NICUs across five states (n=4556 infants).Results:Of the 4120 infants with complete screens, 92% did not have prenatal CHD diagnosis or echocardiography before screening, 72% were not receiving oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 19 publications
1
14
0
9
Order By: Relevance
“…These issues could be addressed or minimized by implementing quality metrics and through the use of electronic decision support tools [33,36]. Best practices are still being developed with regards to screening special populations, particularly home births, births at altitude, and evaluating whether screening of infants in neonatal intensive care units is effective [37]. Colorado requires CCHD screening of infants born at moderate altitude, accepting a higher false positive rate when compared to infants born at sea level [38].…”
Section: Lessons Learnedmentioning
confidence: 99%
“…These issues could be addressed or minimized by implementing quality metrics and through the use of electronic decision support tools [33,36]. Best practices are still being developed with regards to screening special populations, particularly home births, births at altitude, and evaluating whether screening of infants in neonatal intensive care units is effective [37]. Colorado requires CCHD screening of infants born at moderate altitude, accepting a higher false positive rate when compared to infants born at sea level [38].…”
Section: Lessons Learnedmentioning
confidence: 99%
“…No CCHD was detected in this study. 18 Overall, these studies suggest that in asymptomatic infants in the NICU being monitored by a pulse oximeter, the addition of a pulse oximeter-based screen, performed either 24 to 48 hours after admission or before discharge would not detect additional infants with CCHD.…”
Section: Current Evidence: a Literature Reviewmentioning
confidence: 87%
“…17 An NICU-specific multicenter collaborative found that the number of infants not screened according to the protocol was approximately 1.1%. 18…”
Section: Discussionmentioning
confidence: 99%